Korea Południowa – doświadczenia dwóch kryzysów finansowych - Mitręga-Niestrój, Krystyna (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2015)
The article analyzes South Korean experiences of the 1997 and 2008–2009financial crises. The article describes the conditions which led to the 1997 financialcrisis and attempts to answer the question whether similar factors have takenplace in 2008. It also describes the consequences of the crises, especially for thebanking industry and on the financial market. The article also presents a shortoverview of the most important measures taken by the Korean authorities in faceof the Asian crisis. The two analyzed financial crises have some common characteristics,such as a strong decrease in the value of financial assets and the negativeconsequences in the economy. However, Korea faced the global financial crisisstrengthened thanks to the reforms of financial institutions.